2013
DOI: 10.3109/10641955.2013.784788
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characterization and outcomes of preeclampsia with normal angiogenic profile

Abstract: Objective-The objective of this study was to compare the clinical characteristics and outcomes of preeclamptic women presenting with a normal plasma angiogenic profile with those subjects that are characterized by an abnormal angiogenic profile.Methods-This was a secondary analysis of a prospective cohort study in women presenting to obstetrical triage at <37 weeks of gestation and diagnosed with preeclampsia within 2 weeks of enrollment and in whom angiogenic factors (sFlt1 and PlGF) measurements were availab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
107
0
7

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 142 publications
(114 citation statements)
references
References 33 publications
0
107
0
7
Order By: Relevance
“…The observation of low and high PlGF levels 56) and, similarly a high sFlt-1/PlGF ratio ≥ 85 (angiogenic preeclampsia) and a low sFlt-1/PlGF ratio < 85 (nonangiogenic preeclampsia), 57) across pregnancy among women who develop preeclampsia may be an important finding in relation to the pathophysiology and study of preeclampsia. Perhaps these different patterns of PlGF indicate that half of the preeclampsia cases result from insufficient angiogenic signaling (low PlGF), whereas the other half result from insensitivity to angiogenic signaling (high PlGF) or are determined by a different pathogenic factor.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…The observation of low and high PlGF levels 56) and, similarly a high sFlt-1/PlGF ratio ≥ 85 (angiogenic preeclampsia) and a low sFlt-1/PlGF ratio < 85 (nonangiogenic preeclampsia), 57) across pregnancy among women who develop preeclampsia may be an important finding in relation to the pathophysiology and study of preeclampsia. Perhaps these different patterns of PlGF indicate that half of the preeclampsia cases result from insufficient angiogenic signaling (low PlGF), whereas the other half result from insensitivity to angiogenic signaling (high PlGF) or are determined by a different pathogenic factor.…”
Section: R E T R a C T E Dmentioning
confidence: 99%
“…8,[11][12][13][14][15][16] Few adverse outcomes occur in the absence of angiogenic factor abnormalities. 17,18 Although previous studies have detected changes in myocardial function in HDP, 19,20 a direct association between preeclampsia biomarkers, including sFlt1 and sEng, has not been described. In other abnormal cardiovascular states such as congestive heart failure, increased circulating levels of antiangiogenic proteins have been associated with development of endothelial vascular dysfunction, myocardial dysfunction, and adverse cardiovascular outcomes.…”
mentioning
confidence: 97%
“…Verlohren et al (2012) also assessed the value of serum sFlt-1/PlGF as prognostic markers, showing an increased risk of imminent delivery in preeclamptic women with high sFlt-1/PLGF ratios. In addition, Rana et al (2013) showed that women diagnosed with preeclampsia, but with a normal plasma angiogenic profile, are not at risk for adverse maternal or fetal outcomes. Chappell et al (2013) formance of plasma PlGF alone for prediction of delivery for preeclampsia within 14 d in women at ,35 wk with suspected preeclampsia.…”
Section: Angiogenic Factors As Biomarkersmentioning
confidence: 99%